On the Dirichlet problem for Beltrami equations with sources in simply connected domains - Gutlyanskiĭ, V.Ya.; Nesmelova, O.V.; Ryazanov, V.I.; Yakubov, E. (Доповіді НАН України, 2024)
The first 3 authors are partially supported by the Grant EFDS-FL2-08 of the found of the European Federation of Academies of Sciences and Humanities (ALLEA).